If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(x-3)=5(x+5)
We move all terms to the left:
6(x-3)-(5(x+5))=0
We multiply parentheses
6x-(5(x+5))-18=0
We calculate terms in parentheses: -(5(x+5)), so:We get rid of parentheses
5(x+5)
We multiply parentheses
5x+25
Back to the equation:
-(5x+25)
6x-5x-25-18=0
We add all the numbers together, and all the variables
x-43=0
We move all terms containing x to the left, all other terms to the right
x=43
| 4g+32=7+49 | | (x^2+8)/x=0 | | -6(-4x+4)=4 | | w+9/3=5 | | A=L(1-r) | | (x+2)=-2-x | | 7x-(6x+5)=3x-31 | | (4m-7)/2=10 | | 8+2x-16=x+2 | | C(x)=25x+20/ | | (5x-x)=x+3 | | 2p−10+7=9 | | 9=2(p−5)+7 | | 5(4-x)=3x-2 | | -8=1/9(-9x+27) | | 28-71=x/64 | | 5x/2-×=x/10-21/5 | | 6-3(a-5)=7(-2a+3) | | 3(2x+2)+x+5=-30 | | .5-12=3+2n | | 5/6b+7=7/8b+19 | | 7h-21=6 | | 8+2-16=x+2 | | 5.6/(2.5p)=9.6 | | 6x+10=9x+15-3x | | 3h-6=4 | | Z=2(5z^2+3z+7) | | 5/6=10/(w+3) | | 20+4c=-36 | | |x+1|+7=4 | | 7(2+n)-5n=3(6+3n)+3 | | -5x+68=62 |